Woman-centered Brazilian cinema : filmmakers and protagonists of the twenty-first century - Draper, Jack A., III, 1976-; Rêgo, Cacilda (SUNY series in Latin American cinema., 2022)
Illuminates the complex factors that have helped or hindered creative work by and about women in the twenty-first-century Brazilian film industry.